Sustained virologic response achieved after curative treatment of hepatitis C virus‐related hepatocellular carcinoma as an independent prognostic factor. Issue 7 (July 2015) - Kanogawa, Naoya; Ogasawara, Sadahisa; Chiba, Tetsuhiro; Saito, Tomoko; Motoyama, Tenyu; Suzuki, Eiichiro; Ooka, Yoshihiko; Tawada, Akinobu; Kanda, Tatsuo; Mikami, Shigeru; Azemoto, Ryosaku; Kaiho, Takashi; et al.
Abstract Background and Aim Whether an antiviral interferon (IFN)‐based therapy (IBT) after curative treatment of hepatocellular carcinoma (HCC) improves the prognosis in patients with hepatitis C virus (HCV)‐related HCC remains to be elucidated. Methods A total of 178 patients within the Milan criteria underwent curative treatment for HCV‐related HCC. Both the time to beyond the Milan criteria (TTBMC) and overall survival (OS) were compared between the sustained virologic response (SVR) (IFN with SVR, n = 22), non‐SVR (IFN without SVR, n = 19), and non‐IBT (control, n = 82) groups using propensity score matching analysis. Prognostic factors to predict survival were also determined by the Cox proportional‐hazards model. Results TTBMC in the IFN with SVR group was significantly longer than those in the control and IFN without SVR groups (P < 0.001 and P = 0.006, respectively), although no significant difference existed between the IFN without SVR and control groups. Similarly, OS of the IFN with SVR group was significantly longer than that of the control and IFN without SVR groups (P < 0.001 and P = 0.029, respectively), although no significant difference existed between the IFN without SVR and control groups. The Cox proportional‐hazards model identified SVR as an independent prognostic factor in these patients. The IFN with SVR group showed a 0.096‐fold decrease in mortality risk compared with the control group (95% confidence intervals = 0.023–0.405; P = 0.001). Conclusion Elimination of HCV after curative treatment of patients with HCC within the Milan criteria inhibits recurrence and contributes to a preferential prognosis.